FACTORS AFFECTING THE QUALITY OF POSTGRADUATE RESEARCH IN STATE AGRICULTURAL UNIVERSITIES (SAUs) - T. SRINIVAS*, T. V. SRIDHAR, P. PUNNA RAO and T. RAMESH BABU, (The Journal of Research ANGRAU, 2019)
The study conducted on assessing the quality of postgraduate research revealed that the student researchis being amply published and on an average two publications are being brought out from each thesis. Frompostgraduate research, more than 60 per cent of the publications were published in journals having NAASrating